Assessment of genetic diversity in EMS-induced porang (Amorphophallus muelleri Blume) revealed by RAPD markers - Haritzah, Rendha Maulana; Radita, Novia Fitri; Ramadanti, Isma Salsabila; Azzahro, Yusri Despa; Wahyudi, Didik; Resmisari, Ruri Siti; Suyono (Universitas Muhammadiyah Surakarta, 2026)
Increasing genetic diversity of porang through mutation is urgently needed since porang has low genetic diveristy. Therefore, this study aims to increase the genetic diversity of porang using ethyl methanesulfonate (EMS) and analyze the genetic diversity of porang using RAPD markers. Porang explants were subjected to in vitro EMS induction at various concentrations (control, 0.1%, 0.2%, 0.3%, 0.4%, and 0.5%) and evaluated after 35 days. DNA amplification was carried out using 20 RAPD primers. Genetic diversity within and between porang populations was analyzed using POPGENE software, while cluster analysis was performed using PAST software to identify genetic diversity patterns. The results showed that EMS mutation induction effectively increased the genetic diversity of porang. Primers OPA-2 and OPA-9 were identified as the most effective primers for detecting genetic diversity resulting from mutation induction. The 0.2% EMS treatment is recommended because it produced the most notable genetic changes compared to the control and shows potential for generating superior mutants to support porang breeding programs.